Kant, Schiller, Obligation and Chimerical Ethics - Feldhaus, Charles (Studia Kantiana, 2017)
This study analyzes the debate between Kant and Schiller about the role of feelings in the moral sphere based on the concept of obligation (Verbindlichkeit) and the concept of chimerical ethics. The concept of obligation is a central concept in all development of ethics of Kant from the Prize Essay (1763) on. The notion of obligation plays an important role in the debate between Kant and Schiller, since Kant said the concept of duty and the concept of grace could not be harmonized as Schiller thought with the figure of the beautiful soul in Grace and Dignity (1793). Kant discusses the notion of the chimerical ethics in the Lectures on Ethics based on the Baumgarten and Meier. One main characteristic of a chimerical ethical is imposed to human beings to perform an obligation that exceeds the human capacity. One could say that the concept of chimeric ethics influences the conception of moral fanaticism of the Critique of Practical Reason of Kant and the refusal of the ideal of perfection of Stoic ethics. In the debate between Kant and Schiller, the main point of divergence between them is about the possibility of realizing the ideal of moral perfection contained in the concept of the beautiful soul.